Exercise-associated iron deficiency: A review and recommendations for practice - Goldstein, E. R (Strength and Conditioning Journal, 2016)
Iron deficiency is prevalent in female athletes and can impede endurance performance (i.e., slower time trial), and with anemia can reduce endurance capacity. Levels of hepcidin are elevated after exercise second to inflammatory stimuli (interleukin-6) and may contribute to the development of iron deficiency. Hepcidin acts to internalize and degrade ferroportin (cellular channel responsible for iron efflux). This results in sequestration of iron within macrophages, which recycle iron from aged and damaged erythrocytes. Prolonged high-intensity training, especially a modality that includes repetitive foot strikes, can cause hemolysis resulting in upregulation of hepcidin and may contribute to the development of iron deficiency.